2002
DOI: 10.1097/00004770-200208000-00011
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Two Different Root Canal Sealers and Smear Layer on Resistance to Root Fracture

Abstract: The purpose of this in vitro study was to test the effect of Ketac-Endo (KE) and AH 26 on resistance to root fracture and also to evaluate the effect of smear layer. Seventy-two human maxillary canine teeth were randomly divided into six groups (n = 12) and were prepared using six different methods: group 1: KE, without smear layer (smear -); group 2: KE, with smear layer (smear +); group 3: AH 26, smear (-); group 4: AH 26, smear (+); group 5 (negative control): nonprepared; group 6 (positive control): prepar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
62
1
4

Year Published

2005
2005
2018
2018

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 64 publications
(73 citation statements)
references
References 16 publications
4
62
1
4
Order By: Relevance
“…In the present study, no differences in fracture strength were found among roots fi lled with AH Plus, iRoot SP, and MTA Fillapex. The results of this study agreed with those of Karapinar Kazandag et al 5) and and Cobankara et al 30) in that all the experimental groups showed signifi cantly superior fracture resistance than the negative control group. On the other hand, our results contradicted with those of Grande et al 36) and Kim et al 37) , in that they found no clear benefi ts with the use of root canal sealers in improving the fracture resistance of root canal dentin.…”
Section: Effect Of Root Canal Sealers On Fracture Resistance Of Rootfsupporting
confidence: 92%
See 1 more Smart Citation
“…In the present study, no differences in fracture strength were found among roots fi lled with AH Plus, iRoot SP, and MTA Fillapex. The results of this study agreed with those of Karapinar Kazandag et al 5) and and Cobankara et al 30) in that all the experimental groups showed signifi cantly superior fracture resistance than the negative control group. On the other hand, our results contradicted with those of Grande et al 36) and Kim et al 37) , in that they found no clear benefi ts with the use of root canal sealers in improving the fracture resistance of root canal dentin.…”
Section: Effect Of Root Canal Sealers On Fracture Resistance Of Rootfsupporting
confidence: 92%
“…Other favorable features of this sealer include osteoconductivity, hydrophilicity, adhesiveness and chemical bonding to root canal dentinal walls. In several studies, it was shown that chemical bonding to root dentin improved the resistance of endodontically treated teeth against root fractures 7,8,30) . Another newly introduced root canal sealer is MTA Fillapex.…”
Section: Effect Of Root Canal Sealers On Fracture Resistance Of Rootfmentioning
confidence: 99%
“…Variations in the dimensions of the roots, extraction time, and storage conditions may affect the results. 7 According to Versluis et al 8 root canal preparations that resulted in a round cross-section led to more uniform stress distributions within a root during filling, thereby reducing fracture susceptibility.…”
Section: Discussionmentioning
confidence: 99%
“…Bununla birlikte, kuvvetin dişin uzun eksenine dik olarak uygulanmas›n›n kuvvetin uniform olarak iletilmesini sağlad›ğ› bildirilmiştir (25, 26). Bu çal›şmada, örneklerin k›r›lma dirençlerinin değerlendirilmesi için, birçok çal›şmada olduğu gibi (8,27, 28) kuvvet köklere dik yönde uyguland›. Resilon ve Epiphany patlar›n› değerlendi-ren birçok çal›şma vard›r (8,28,33,34 Epiphany sistemi ile postlar› hasta baş›nda harcanan tedavi zaman› aç›s›ndan karş›laşt›rd›-ğ›m›z da post sistemleri ile yap›lan kanal tedavilerinde ilk önce kanal tedavisi yap›l›p tekrar bu kanal›n sökülmesi için ekstra zaman harcanmaktad›r.…”
Section: Discussionunclassified